2019
DOI: 10.1080/0361526x.2020.1696622
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Sustaining Publication of a Newly Created Undergraduate Research Journal

Abstract: Once the excitement of creating a new journal fades and publication begins, a new challenge arises in sustainability. Augusta University published the first issue of their undergraduate research journal, The Arsenal, in 2016. Although the first two issues received consistent submissions and timely processing by the peer-reviewers, several unanticipated factors have influenced the journal's continued publication. Some of these factors include graduation of the student editorial board, faculty turnover, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Many reasons are identified why journal articles are rejected. They arise from different flaws in the research design, manuscript organization, results and discussion, conclusion (Ahlstrom, 2012;Akhtar, 2008;Fischer et al, 2017;Holschuh, 1998;Johnson, Putnam Davis, & Bandy, 2020;Pimm, 2013;Stivers & Cramer, 2017;Sullivan, 2015). Ezeala Nweke & Ezeala (2013) studied the common errors in the manuscript submitted to medical science journals in Asia and Africa showed that out of 42 papers analyzed, they found crucial flaws in every section of the document.…”
Section: Introductionmentioning
confidence: 99%
“…Many reasons are identified why journal articles are rejected. They arise from different flaws in the research design, manuscript organization, results and discussion, conclusion (Ahlstrom, 2012;Akhtar, 2008;Fischer et al, 2017;Holschuh, 1998;Johnson, Putnam Davis, & Bandy, 2020;Pimm, 2013;Stivers & Cramer, 2017;Sullivan, 2015). Ezeala Nweke & Ezeala (2013) studied the common errors in the manuscript submitted to medical science journals in Asia and Africa showed that out of 42 papers analyzed, they found crucial flaws in every section of the document.…”
Section: Introductionmentioning
confidence: 99%